Geotechnical Earthquake Zonation of Semnan Region Based on Geophysical Tests Results - Dr.Hamed Javdaniyan; Dr.Abdolhosein Hadad; Alireza Mirnejad (جغرافیا و آمایش شهری منطقه‌ای, 2018)
Geotechnical earthquake zonation as one of the most important factors necessary for town and country arrangement and also development of different region, is able to provide valuable information on the studied areas. In this study, based on a wide range of geophysical test results in Semnan City, iso-velocity maps of shear wave and iso-depth maps of shear wave velocity were provided using ArcGIS program. Using iso-velocity maps of shear wave, seismic bedrock depth was determined through three different criteria for Semnan City area. Seismic bedrock depth in Semnan City was measured from about 5 to 30 meters according to the Standard 2800. Based on zonation and according to the nature and type of sediments, southeast of Semnan have greatest depth and northeast have the lowest depth of seismic bedrock. The average shear wave velocity varies between 427 and 804 meters per second in the depth up to 30 meters. In general, from the northern to the southern part of the city, the average shear wave velocity decreases and the depth of seismic bedrock increases. Furthermore, soil was classified using the study results and based on the Standard 2800 and European Regulation. The results showed that Semnan City area often falls into group II according to the Standard 2800 and mainly into group B based on the European Regulation.